The passage of nature - Emmet, Dorothy M. 1904-2000 (Macmillan, 1992)
The concept of Process is often used, but seldom discussed. In this book, Dorothy Emmet treats the idea as a key concept in describing what goes on in the world. She shows how a process differs from a succession of events, facts, or just things changing, and claims that causation should be seen in terms of processes. Delineating three kinds of process, or "goings on"--artificial, as in the building of a house; natural, as in physiological changes; and social, as in human political activities--she describes their general characteristics as well as the special characteristics of organic and social processes. Finally, she explores the possible significance of the notion of process for morals and religion and proposes what might be called "providential processes." As her title suggests, the author acknowledges the influence of an early interest in Alfred North Whitehead's philosophy of process, and she critically discusses some of his views. But this is not an exegesis of Whitehead; it is an original metaphysical theory in which creativity in the passage of nature comes through the activities of things and persons sustaining processes.
Keywords: Procesfilosofie; Metaphysics; Process philosophy; Prozessphilosophie; Natur